Histone H2A‐H2B binding by Pol α in the eukaryotic replisome contributes to the maintenance of repressive chromatin. (13th August 2018) - Evrin, Cecile; Maman, Joseph D; Diamante, Aurora; Pellegrini, Luca; Labib, Karim
Abstract: The eukaryotic replisome disassembles parental chromatin at DNA replication forks, but then plays a poorly understood role in the re‐deposition of the displaced histone complexes onto nascent DNA. Here, we show that yeast DNA polymerase α contains a histone‐binding motif that is conserved in human Pol α and is specific for histones H2A and H2B. Mutation of this motif in budding yeast cells does not affect DNA synthesis, but instead abrogates gene silencing at telomeres and mating‐type loci. Similar phenotypes are produced not only by mutations that displace Pol α from the replisome, but also by mutation of the previously identified histone‐binding motif in the CMG helicase subunit Mcm2, the human orthologue of which was shown to bind to histones H3 and H4. We show that chromatin‐derived histone complexes can be bound simultaneously by Mcm2, Pol α and the histone chaperone FACT that is also a replisome component. These findings indicate that replisome assembly unites multiple histone‐binding activities, which jointly process parental histones to help preserve silent chromatin during the process of chromosome duplication. Synopsis: Replisome assemblies unite multiple histone‐binding activities that jointly process parental histones during DNA replication. Among them, polymerase α has a particular role via histone H2A‐H2B binding to preserve gene silencing at budding yeast telomeres and mating‐type loci. Ctf4‐dependent Pol α replisome tethering is dispensable for efficient DNA synthesis but required for maintenance of repressive chromatin. The Pol α catalytic subunit contains a conserved histone‐binding motif similar to the motif in Mcm2 helicase subunit. Unlike H3‐H4 binding by Mcm2, the Pol α motif binds histones H2A‐H2B. Mutation of either Pol α or Mcm2 histone‐binding motifs abrogates gene silencing at telomeres and mating‐type loci. Abstract : One of several replisome‐associated histone‐binding activities for processing parental histones during replication has a particular role in preserving gene silencing at budding yeast telomeres and mating‐type loci.